Meningkatkan Pembelajaran Penjumlahan Bilangan melalui Project Based Learning bagi Anak Tunagrahita - Yantrisna, Irma; Iswari, Mega (Universitas Negeri Padang, 2023)
This research is motivated by problems at SLB Autisma Mutiara Bangsa Pratama Padang in mentally retarded children in class VII where the results of children's mathematics learning are still low in the material of adding numbers. The purpose of this research is to see the process of implementing learning in the addition of numbers and to improve the learning outcomes of class VII children with the material of adding numbers through a project based learning model. The type of research used by researchers is classroom action research which consists of two cycles, each cycle having stages namely, planning, implementing, observing and reflecting. Based on the research results, it was found that the project based learning learning model can improve the learning process seen by independent children and can improve learning outcomes in the addition of numbers material, which can be seen from the results that increase in each cycle.